The royal secret [large type] - Taylor, Andrew, 1951 October 14- (James Marwood and Cat Lovett;, 2022)
"From the No.1 bestselling author of The Last Protector and The Ashes of London comes the next book in the phenomenally successful series following James Marwood and Cat Lovett during the time of King Charles II. Two young girls plot a murder by witchcraft. Soon afterwards a government clerk dies painfully in mysterious circumstances. His colleague James Marwood is asked to investigate - but the task brings unexpected dangers. Meanwhile, architect Cat Hakesby is working for a merchant who lives on Slaughter Street, where the air smells of blood and a captive Barbary lion prowls the stables. Then a prestigious new commission arrives. Cat must design a Poultry House for the woman that the King loves most in all the world. Unbeknownst to all, at the heart of this lies a royal secret so explosive that it could not only rip apart England but change the entire face of Europe."--